DESAIN RAK BUKU BERBENTUK PEPOHONAN PINUS DARI JANGGEL JAGUNG DAN RESIN POLIMER - Adiani, Ningroom (JURNAL KREATIF: DESAIN PRODUK INDUSTRI DAN ARSITEKTUR, 2017)
Organic waste can be as an alternative to wood material on the bookcase. Corncob is an organic waste that can be used as a material to make it. By reinforcing polyester resin on corncob board composition, the bookshelves will producing to transform by pine trees. This form is taken to try to make a bookcase composed of blunt and sharp corners, where the bookshelves generally having a 900 angle.The steps in creating a work with corncob reinforced polyester resin need to be explained and elaborated in detail. Several problems arise in the process of embodiment, among others: the technique of making the composition of corncob to be aligned board of transform by pine trees, the form of transformation is preferred to the lines, fields and textures that according to the form of pine tree/pine trees; additional construction as the reinforcement of the shape, and construction of the reinforcement to strengthen the transformer.The design method according to Gustami method that it is three stages-six steps, which will be used to realize this product. The embodiment of corncob fields with blunt and sharp corners is used to obtain the shelves of transformation of pine trees. Some techniques of connection in wood are also used in this material, because of the resemblance of corncob material with the wooden.This product is expected to inspire design for other furniture products. The angled shape of the board other than the elbows on the bookshelf can be used as a reference to be developed in a subsequent study, that will improve the use of corncob and polyester resin matters.